2018
DOI: 10.1002/aoc.4425
|View full text |Cite
|
Sign up to set email alerts
|

Benedict's solution/ vitamin C: An alternative catalytic protocol for the synthesis of regioselective‐1,4‐disubstituted‐1H‐1,2,3‐triazoles at room temperature

Abstract: A novel and highly efficient method for the synthesis of 1,4‐disubstituted‐1H‐1,2,3‐triazoles by copper‐catalyzed azide‐alkyne cycloaddition has been developed. This economic and sustainable protocol uses a readily available Benedict's solution/Vitamin C catalyst system affording a wide range of 1,4‐disubstituted‐1H‐1,2,3‐triazoles under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 83 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The catalytic activity of Fe 3 O 4 @SiO 2 /EP.EN.EG.Cu was compared with various reported catalysts in the literature toward the synthesis of 1,4‐disubstituted 1,2,3‐triazoles. It was observed that Fe 3 O 4 @SiO 2 /EP.EN.EG.Cu promotes the yield of products and reaction time effectively in comparison with other catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic activity of Fe 3 O 4 @SiO 2 /EP.EN.EG.Cu was compared with various reported catalysts in the literature toward the synthesis of 1,4‐disubstituted 1,2,3‐triazoles. It was observed that Fe 3 O 4 @SiO 2 /EP.EN.EG.Cu promotes the yield of products and reaction time effectively in comparison with other catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Then, copper(I) triazolide intermediate ( I‐8 ) is formed by reductive ring contraction. Finally, copper(I) triazolide intermediate gives a proton from an alkyne to produce triazole products (Scheme ) …”
Section: Mechanism Aspects Of the Copper‐catalyzed Click Reactionmentioning
confidence: 99%
“…[20,21] Although many metals such as zinc (Zn), silver (Ag), nickel (Ni) and gold (Au) have been reported as coupling catalysts, [22] Cu (I) is commonly used for this aim. [23][24][25][26] The coppercatalysed alkyne-azide cycloaddition (CuAAC) reaction represents the flagship transformation of "Click Chemistry" that has considerable applications in organic synthesis, coordination chemistry and material science. [27] With over 2,000 documented reports in about a decade, the CuAAC reaction is notable and undoubtedly has been a breakthrough in organic synthesis and Cu (I) catalysis.…”
Section: Introductionmentioning
confidence: 99%